Light-enhancing ketone transfer hydrogenation catalyzed by diphosphine phenanthroline ruthenium complexes - Masson, Gustavo Henrique Cicero [UNESP]; Ballico, Maurizio; Goi, Beatriz Eleutério [UNESP]; de Carvalho-Jr, Valdemiro Pereira [UNESP]; Baratta, Walter (Elsevier, 2024)
The cationic phenanthroline ruthenium derivatives [Ru(OAc)(dppb)(NN)]OAc (NN = phen 1, imidazo[4,5-f][1,10]phenanthroline 2) have been obtained in high yield by reaction of the acetate [Ru(OAc)2dppb] with the corresponding NN ligand. The dinuclear cyclometalated [(dppb)(η2-OAc)(Ru(µ-NN-phenimid-NC)Ru(η2-OAc)(dppb)]OAc (3) has been prepared from 2 with [Ru(OAc)2(dppb)] via elimination of acetic acid. The characterization of these compounds has been carried out by NMR, FT-IR, UV–Vis, conductivity and cyclic voltammetry measurements. These derivatives display catalytic activity in the transfer hydrogenation of aromatic and aliphatic cyclic ketones at S/C up to 2000 in presence of NaOiPr in 2-propanol. An increase of the rate (up to 8 times) has been observed upon irradiation at 30 and 60 °C (300 W Xenon Arc Lamp light source). Control experiments show that [Ru(OiPr)2(dppb)(phen)] (1A), formed from 1 by substitution of the acetate with the isopropoxide ligand, shows a stronger emission compared to 1 and that 1A is quenched by NaOiPr, affording the dihydride [Ru(H)2(dppb)(phen)] (1C) via a photo induced β-H elimination.
Keywords: Photo-TH; Photo-trasfer hydrogenation; Photochemistry; Ruthenium complexes